Common Site of Urinary Calculi in Kidney, Ureter and Urinary Bladder Region: Jos Experience - Danjem, Samuel Moses; AJ, Salaam; Yunusa HO, Kolade-; SI, Shuaibu (International Journal of Scientific Research and Management (IJSRM), 2019)
Objective: To determine the common location of calculus along the urinary tract using CT scan. Methods: This cross sectional study was conducted using CT from November 2016 to September 2018, in a tertiary hospital in Jos, Nigeria. The CT images acquired from this period were evaluated and 50 patients were positive for urolithiasis. The data was subjected to statistical analysis based on age, gender and calculus location.Results: Out of the 50 patients with calculi, 34 were males and 16 were females with a male to female ratio of 2.13:1. 137 urinary calculi were documented in which 90 were in males and 47 in the female patients. Highest occurrence of calculi was seen in age group 31-40 years (34.0%). 112(82%) were renal stones, 12(9%) were ureteric stones, 8(6%) were found in pelvi-ureteric junction (PUJ), 3(2%) were in the vesico-ureteric junction (VUJ), 2(1%) were in the urinary bladder and none in the urethra.Conclusion: Kidney stones are the most common followed by the ureter, the pelvi-ureteric junction, the vesico-ureteric junction and the bladder.